Betahistine dihydrochloride quantitative determination in dosage forms by the reaction with sodium 1,2-napthoquinone- 4-sulphonate - Donchenko, А. O.; Vasyuk, S. O; Донченко, А. А.; Васюк, С. А.; Донченко, Анастасія Олександрівна; Васюк, Світлана Олександрівна (Запорізький державний медичний університет, 2018)
Objectives. Spectrophotometric method is one of the most convenient methods in pharmaceutical analysis, as it is sensitive, precise and cost effective. Therefore, the aim of the present work was the development of simple and available method for the quantitative determination of betahistine dihydrochloride in dosage forms. Materials and methods. Sodium 1,2-napthoquinone-4-sulphonate was assessed as chemical reagent for the quantitative determination of betahistine dihydrochloride by visible spectrophotometric method. Results. Different variables affecting the reactions between sodium 1,2-napthoquinone-4-sulphonate and the drug were carefully studied and optimized. It was established that betahistine dihydrochloride reacts with sodium 1,2-napthoquinone-4-sulphonate in alkaline medium with the colored reaction product formation with absorption maximum at 485 nm. The proposed method was subjected to validation tests. The method was validated for the parameters like linearity, precision, accuracy, robustness and scope of application. Beer’s law was obeyed over the concentration range of 2.40–4.00 mg/100 ml. Parameters of linear dependence were calculated with the help of regression analysis by means of least squares. Coefficients of stoichiometric relationship were also determined by means of molar ratios and continuous changes. The proposed procedure meets the requirements of State Pharmacopoeia of Ukraine that are made for dosage forms. Conclusion. On the basis of the carried out investigations of betahistine dihydrochloride quantitative determination, spectrophotometric procedure has been developed and validated. This procedure is successfully applied for dosage forms analysis. Investigation results show that the procedure is highly sensitive, precise, simple in performance and relevant to be applied at the quality control laboratories for dosage forms. Цель работы – разработка простой и доступной методики количественного определения бетагистина дигидрохлорида в лекарственных формах. Материалы и методы. Натриевую соль 1,2-нафтохинон-4-сульфокислоты оценивали как химический реагент для количественного спектрофотометрического определения бетагистина дигидрохлорида. Результаты. Различные факторы, влияющие на взаимодействие между натриевой солью 1,2-нафтохинон-4-сульфокислоты и лекарственным веществом, тщательно изучены и оптимизированы. Установлено, что бетагистина дигидрохлорид реагирует с натриевой солью 1,2-нафтохинон-4-сульфокислоты в щелочной среде с образованием окрашенного продукта реакции с максимумом абсорбции при 485 нм. Проведена валидация разработанной методики. Проверены основные валидационные характеристики: линейность, прецизионность, правильность, робастность и диапазон применения. Подчинение закону Бера наблюдается в пределах концентрации 2,40–4,00 мг/100 мл. Параметры линейной зависимости рассчитали с помощью регрессионного анализа методом наименьших квадратов. Также определены коэффициенты стехиометрических соотношений методами молярных соотношений и непрерывных изменений. Предложенная методика соответствует требованиям ГФУ, которые предъявляют к методикам количественного анализа лекарственных веществ. Выводы. На основе проведенных исследований разработана и валидирована спектрофотометрическая методика количественного определения бетагистина дигидрохлорида, которая успешно применена для анализа лекарственных форм. Результаты исследования свидетельствуют, что методика является высокочувствительной, точной, простой в исполнении и пригодной для использования в лабораториях контроля качества лекарственных веществ. Мета роботи – розробка простої та доступної методики кількісного визначення бетагістину дигідрохлориду в лікарських формах. Матеріали та методи. Натрієву сіль 1,2-нафтохінон-4-сульфокислоти оцінювали як хімічний реагент для кількісного спектрофотометричного визначення бетагістину дигідрохлориду. Результати. Різноманітні чинники, що впливають на взаємодію між натрієвою сіллю 1,2-нафтохінон-4-сульфокислоти та лікарською речовиною, ретельно вивчені, оптимізовані. Встановили, що бетагістину дигідрохлорид реагує з натрієвою сіллю 1,2-нафтохінон-4-сульфокислоти в лужному середовищі з утворенням забарвленого продукту реакції з максимумом абсорбції при 485 нм. Виконали валідацію розробленої методики. Перевірили основні валідаційні характеристики: лінійність, прецизійність, правильність, робастність і діапазон застосування. Підпорядкування закону Бера спостерігають у межах концентрації 2,40–4,00 мг/100 мл. Параметри лінійної залежності розрахували за допомогою регресійного аналізу методом найменших квадратів. Визначили коефіцієнти стехіометричних співвідношень методами молярних співвідношень і неперервних змін. Запропонована методика відповідає вимогам ДФУ, що ставлять до методик кількісного аналізу лікарських речовин. Висновки. На підставі досліджень розроблено та валідовано спектрофотометричну методику кількісного визначення бетагістину дигідрохлориду, котру успішно застосували для аналізу лікарських форм. Результати дослідження свідчать, що методика є високочутливою, точною, простою у виконанні та придатною для використання в лабораторіях контролю якості лікарських речовин.
Количественное определение бетагистина дигидрохлорида в лекарственных формах по реакции с натриевой солью 1,2-нафтохинон-4-сульфокислоты
Кількісне визначення бетагістину дигідрохлориду в лікарських формах за реакцією з натрієвою сіллю 1,2-нафтохінон-4-сульфокислоти
Keywords: validation studies; spectrophotometry; sodium 1,2-napthoquinone4-sulphonate; betahistine dihydrochloride; валідація; спектрофотометрія; натрієва сіль 1,2-нафтохінон4-сульфокислоти; бетагістину дигідрохлорид; валидация; спектрофотометрия; натриевая соль 1,2-нафтохинон4-сульфокислоты; бетагистина дигидрохлорид